O dever de motivação e o problema da fundamentação simbólica das decisões judiciais - Souza, Leonardo Vieira de (2021)
This paper’s focus is the justification of judicial decisions and aims to answer the following question: a judicial decision can be grounded on symbolic reasons and still be consistent with the democratic state ruled by the law? As a research cutout, the investigation focuses on judgments rendered by Constitutional Courts. That’s because, in this context, in which the limits of law and politics are close, Courts frequently use non-juridical arguments as justification for its decisions. This research is based on the hypothesis that the reason of judgment is the element that gives legitimacy to the jurisdictional activity. Thus, the normative delimitation of what is meant by acceptable grounds is a necessary element to assess the legitimate limits of the judiciary's performance, in addition to consists in a fundamental duty. The methodology applied was the analysis of cases judged by the Brazilian Supreme Court, selected by sampling based on qualitative criteria. The analysis of the cases confirmed the initial hypotheses that, in the Brazilian model, the Constitutional Court plays a prominent role, validating the performance of the legislature and the executive; when deciding in hard-cases or those characterized by reasonable moral dissent, the Court uses a symbolic foundation, which harms the integrity of the democratic model; finally, considering the risks of using symbolic grounds, the activity of delimitation of an acceptable grounds for judgments gains importance.